Are Individual Differences in Information-Processing Styles Related to Transformational Leadership? A Test of the Cognitive Experiential Leadership Model - Curtis, Guy J.; Wee, Serena (Frontiers in Psychology, 2021)
The recently proposed Cognitive Experiential Leadership Model (CELM) states that leaders’ preference for rational thinking and behavioral coping will be related to their level of transformational leadership. The CELM was based on research that principally used cross-sectional self-report methods. Study 1 compared both self-ratings and follower-ratings of leadership styles with leaders’ self-rated thinking styles in 160 leader-follower dyads. Study 2 compared both self-ratings and coworker-ratings of leadership styles with leaders’ self-rated thinking styles for 74 leaders rated by 607 coworkers. In both Studies, leaders’ rational thinking, imaginative thinking, and behavioral coping correlated positively with their self-rated transformational leadership. However, only behavioral coping, but not rational thinking, was correlated with follower-rated transformational leadership in Study 1 and thinking styles were unrelated to other-rated transformational leadership in Study 2. These results partly support and partly challenge the CELM.